2014
DOI: 10.12809/hkmj144258
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of availability and accessibility of community automated external defibrillators in a territory in Hong Kong

Abstract: The number and accessibility of community automated external defibrillators in this territory are comparable to those in other developed countries. The placement site of community automated external defibrillators is cost-effective. However, the public access defibrillation rate is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…In Hong Kong, there have been investigations on the availability and accessibility of defibrillators in the community. 12,13 However, an organised public access programme is still lacking. In terms of prehospital and in-hospital measures, shorter response times of emergency medical systems, postresuscitation targeted temperature management, and comprehensive post-cardiac arrest care have proven to be effective measures to improve survival.…”
Section: Strategies To Enhance Out-ofhospital Cardiac Arrest Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hong Kong, there have been investigations on the availability and accessibility of defibrillators in the community. 12,13 However, an organised public access programme is still lacking. In terms of prehospital and in-hospital measures, shorter response times of emergency medical systems, postresuscitation targeted temperature management, and comprehensive post-cardiac arrest care have proven to be effective measures to improve survival.…”
Section: Strategies To Enhance Out-ofhospital Cardiac Arrest Survivalmentioning
confidence: 99%
“…For example, a local cardiac arrest registry at the accident and emergency department of Tuen Mun Hospital identified deficiencies in the availability and accessibility of publicly accessible defibrillators. 12 With the implementation of survival enhancement measures, longitudinal data collected using the same collection methodology are required to evaluate their effectiveness.…”
Section: Surveillance Audit and Feedbackmentioning
confidence: 99%
“…27 Knowledge of the location of automated external defibrillators (AEDs) among international travellers is inadequate based on an airport survey. 62 Nonetheless, locations of AEDs should be more publicly accessible to facilitate their retrieval when needed [63][64][65] ; this is particularly crucial if the traveller is not familiar with the surroundings abroad. Technological inventions, e.g., a verified mobile AED map 66 and medical drones, 67 may potentially serve as useful aids for international travellers in the future.…”
Section: Medical Tourismmentioning
confidence: 99%
“…A study of the accessibility and availability of 207 AEDs in 670 facilities in New Territories (NT) West published in 2014 provided some insight into this issue. 40 The investigators found that many of the AEDs (37.7%) were placed in schools in NT West. Whether these AEDs were truly accessible by the public was questionable as schools have limited opening hours.…”
Section: Factors Affecting the Likelihood Of Success Of A Public Accementioning
confidence: 99%